A qualitative study of factors related to cardiometabolic risk in rural men. (December 2016) - Morgan, Emily; Graham, Meredith; Folta, Sara; Seguin, Rebecca
Abstract Background Rural men are known to have poor health behaviors, which contribute to their elevated burden of cardiometabolic disorders in the United States. Although regular physical activity, healthy eating, and avoiding tobacco can reduce cardiometabolic risk, little is known about how to engage rural men in health promotion programs. To bridge this gap in evidence, we investigate knowledge of modifiable cardiometabolic risk factors among rural men in the western United States, identify their concerns related to heart health and motivation to reduce risk, and explore individual, social, and community-level influences on heart-healthy behaviors, specifically diet, physical activity, and tobacco use. Methods We conducted seven focus groups with 54 sedentary, overweight/obese men (mean body mass index [BMI] = 31.3 ± 4.6) aged 43–88 residing in government-designated "medically underserved" rural Montana towns in September and October 2014. All sessions were audio-recorded and transcribed verbatim. Transcripts were coded and analyzed thematically using Nvivo software. Participants also completed a brief questionnaire about personal characteristics and health behaviors. These data were explored descriptively. Results Despite being classified as overweight/obese and sedentary, no participants reported to be in poor health. Many men described health relative to self-reliance and the ability to participate in outdoor recreation; concern with health appeared to be related to age. Participants were generally knowledgeable of heart-healthy behaviors, but many felt fatalistic about their own risk. Catalysts for behavior change included a serious medical event in the household and desire to reduce aging-associated functional decline. Barriers to adopting and maintaining healthy eating and physical activity habits and abstaining from tobacco included normative beliefs around masculinity and individual liberty, the limited social universe of small towns, winter weather, time constraints, and preferences for unhealthy foods. Facilitators included behavioral self-monitoring, exercising with a partner, and opportunities for preferred activities, such as hunting and team sports. Conclusions These findings provide important insight about influences on rural men's health behaviors and provide guidance for possible intervention strategies to promote cardiometabolic health. Trial registration ClinicalTrials.govNCT02499731 . Registered 1 July 2015.